PENGARUH SUPERVISI KEPALA SEKOLAH DAN IKLIM KERJA TERHADAP MOTIVASI KERJA GURU SEKOLAH DASAR DI KECAMATAN KERTASEMAYA KABUPATEN INDRAMAYU - Ayi Meldarena (Edum Journal, 2019)
The purpose of this study was to find out how much influence the principal's supervision and work climate simultaneously had on the motivation of elementary school teachers working in Kertasemaya Subdistrict, Indramayu Regency. The research method used is the survey method with correlational techniques and regression and the collection technique data used are Likert scale questionnaire data on 65 public elementary school teachers in the Kertasemaya sub-district of Indramayu Regency. The results of the study can be concluded that: (1) There is a significant effect of supervision of the principal on the motivation of elementary school teachers working in the sub-district of Kertasemaya, Indramayu Regency. The magnitude of the influence of the principal's supervision of teacher work motivation is 17.3%, while the rest is influenced by other variables. (2) There is a significant effect of work climate on the motivation of elementary school teachers working in Kertasemaya Subdistrict, Indramayu Regency. The magnitude of the influence of the work climate on teacher work motivation is 21%, while the rest is influenced by other variables besides the supervision of the principal, which are not examined in this study (Epsilon). (3) there is a simultaneous significant effect of school principal supervision and work climate on the motivation of elementary school teachers working in Kertasemaya District, Indramayu Regency. The magnitude of the influence of the principal's supervision and the work climate simultaneously on the motivation of elementary school teachers working in Kertasemaya Subdistrict, Indramayu Regency is 32%, while the rest is influenced by other variables, which are not examined in this study (epsilon). To increase work motivation, it is necessary to supervise the principal regularly and need a conducive work climate.